ONLINE MEDIATION – TOOL FOR DISPUTE RESOLUTION DURING LOCKDOWN - Dzimistarishvili Ucha (Legal Bulletin, 2021)
Article reviews the development process and stages of online mediation. Online Dispute Resolution and online mediation became even more important tool due to pandemic situation in whole world, than ever before. Therefore, article aims to discuss advantages and risks for online mediation. Article provides main characteristics of traditional mediation and their link with online mediation tools.